2012
DOI: 10.1002/app.36950
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solvent interactions on the structure and properties of prepared PAni nanofibers

Abstract: The changes of structure and properties of nanofibers were studied as a function of solubility parameters of the organic solvents that are used in interfacial polymerization of polyaniline (PAni) nanofibers. The presence of UV-visible absorbance at 340, 440, and 800 nm confirmed the formation of emeraldine salt structure of the prepared PAni nanofibers. Fourier transform infrared spectral results indicate an increasing trend of benzenoid to quinoid ratio with the decrease of interaction of the solvents with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…This is potentially a great advantage because a large variety of organic solvents can be selected as the organic phase . However, the solubility parameters of the organic solvents used in the interfacial polymerization of PANI nanofibers have an effect on their structure and properties . The difference in the monomer–solvent interaction leads to the variation in the degree of conjugation, domain length, d ‐spacing and strain.…”
Section: Preparation Of Pani Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…This is potentially a great advantage because a large variety of organic solvents can be selected as the organic phase . However, the solubility parameters of the organic solvents used in the interfacial polymerization of PANI nanofibers have an effect on their structure and properties . The difference in the monomer–solvent interaction leads to the variation in the degree of conjugation, domain length, d ‐spacing and strain.…”
Section: Preparation Of Pani Nanofibersmentioning
confidence: 99%
“…57 However, the solubility parameters of the organic solvents used in the interfacial polymerization of PANI nanofibers have an effect on their structure and properties. 58 The difference in the monomer-solvent interaction leads to the variation in the degree of conjugation, domain length, d-spacing and strain. The benzenoid-to-quinoid ratio tends to increase when the interaction of the solvent with aniline decreases, which can be correlated to the increase in the degree of conjugation of the polymer wileyonlinelibrary.com/journal/pi (2) Aniline concentration.…”
Section: Template-free Polymerizationmentioning
confidence: 99%
“…Many studies showed that solvent has a big role on final fiber [21][22][23][24]. Lubasova et al explained what the poor and good solvents are for PVB by applying a Hansen Solubility Parameter (HSP).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the XRD pattern of fumaric acid-doped PANI, two broad bands centered at 21 and 24.8 as reported before [39] and three acute absorption peaks, observed at 2u = 22.74 , 28.72 , 29.32 , represent its partially crystalline structure. The acute peaks at 2u = 22.74 and 28.72 are ascribed to the periodicity parallel and perpendicular to the polymer chains of PANI, respectively [40], different from the typical broad reflections of the HCl-doped PANI at around 19.2 and 26 [41]. Its crystallinity of 27.75% according to the calculation indicates that the dopant of fumaric acid improved the PANI crystallinity.…”
Section: Crystallinitymentioning
confidence: 89%